EFISIENSI DAN PROSPEK BISNIS USAHA BUDIDAYA IKAN PATIN DI KABUPATEN KAMPAR - MUFTI MUFTI; ROZA YULIDA (Universitas Lancang Kuning, 2009)
ABSTRACTThe problem of this research are how about 1) productin factor who influenceprduction patin fish that cultivated in pool; 2) efficiency cultivation patin fish inpool; 3) prospect business cultivation patin fish in future at Kampar regancy, theresearch do at Kampar regency with sample district, XIII Koto Kampar District.Total of responden are 69 people from 137 hausehold fish farmer. Data collectiondo with technique direct interview. Data that taken in one periode production andanalysed with production function Cobb-Douglash model. From research product,we can know potential business fish cultivation at pool at Kampar regency stilllarge that is 2112 hectare, the while has used 645,22 hectare. Area of pool about1.323,4 m2, where smallest area about 200 m2 and largest area 10.000 m2 Scattereddense seeds at pool 8090,87 tails or about 6 tails/m2. total woof given 68 kg orabout 0,97 kg for one fish in one cultivation periode (about 6,7 month). While averageproduction that yield quantity 6.263,70 kg. the based of analyse production functionwith way collective all variable, seeds, woof, large pool variable and periode ofproduction variable influence positive and evident for production patin fish at pool.If seen with separate, seed and woof variable very influence for production patinfish at pool. The while if seen from use of production factor for efficiency business,use of seed and woof production factor not yet efficient